Recommendations for strengthening Blue Carbon science - Dahl, Martin (2025)
Blue carbon (BC) habitats (e.g., mangroves, tidal marshes, and seagrasses) are important CO2 sinks but are among the most threatened ecosystems on Earth. Substantial research over the last decade has quantified BC to evaluate the climate benefits associated with habitat conservation and restoration. However, the exponential growth in BC science has resulted in differing approaches that hinder comparison across studies and increase uncertainty. Here, we synthesized existing data to depict the range of uncertainty associated to different BC methodologies and argue that cumulative biases linked to multiple methodologies can result in BC estimates differing by up to 10-fold. We identified 14 common research procedures that can be improved to strengthen BC biophysical assessments and support implementation of BC projects, and outlined good practices to align research with policy, management, and ethical values. Standardization of practices will help generate high-quality BC projects that can deliver multiple co-benefits for humans and the environment.